EFFECT OF 25%, 37,5% AND 50% MAULI BANANA (Musa acuminata) STEM EXTRACT AS MOUTHWASH ON COLOR STABILITY OF BULK FILL RESIN COMPOSITE - Dewi Puspitasari; Maharani Laillyza Apriasari (FKG Unlam, 2018)
Background:. Mauli banana stem extract can be used as an herbal mouthwash. The use of mouthwash in the oral cavity may be in contact with tissue mucosa, dentition and restorations. Bulk-fill composite resin is currently used as restoration. Composite resins have a tendency to experience discoloration. One of the factors that may cause color changes in composite resins is the use of mouthwash. Purpose: to analyze the effect of 25% mauli banana stem extract, 37.5% and 50% as a mouthwash to the color change in bulk-resin composite resin restoration. Method: This study was purely experimental pretest and posttest group design. Composite resin specimens was fabricated accordingISO 4791: 2000 specifications, molds of 17 mm in diameter and 1 mm thickness. There were 5 treatment groups that composite resin samples were immersed in the distilled as negative control, 25% mauli banana extract solution, 37.5% and 50% and chlorhexidine gluconate as positive control. Data analysis used one way Annova statistical test. Result: there were significant differences in the composite resin group immersed in aquades, chlorhexidine and mauli banana stem extracts, but there was no significant difference in the mauli banana extract stem at different concentrations. Conclusion: mauli banana stem extract causes the highest color change in composite resin when used as a mouthwash.